Effect Of Giving Cork Fish Capsules To Healing Sectio Secarea Surgery Wounds - Andi Indra (Journal of Applied Nursing and Health, 2019)
Sectio caesaria (SC) is a method of giving birth to the fetus using an incision in the stomach and uterus. Wounds after surgery for sectio caesarea will undergo a wound healing process. Cork Fish Capsules are beneficial to postoperative patients, which is to increase their albumin to normal. The Purpose of Knowing the Effect of Cork Fish Capsules on the Healing of Sectio Secarea Surgical Wounds in the Postpartum Room of Torabelo Sigi Hospital. The design used in the study was quasi-experimental. The population is all post SC mothers in the post-partum room at Torabelo Sigi Hospital. The sample size was 20 respondents using the Independent Variable Purposive sampling technique. The research was the administration of cork fish capsules. The dependent variable is wound healing. Data was collected using a questionnaire, then the data were analyzed using the Wilcoxon test with a significance level of α ≤ 0.05 The results showed that almost all respondents in the experimental group had moderate wound healing before the intervention as many as 9 respondents (90%), had good wound healing after intervention as many as 9 respondents (90%), most of the control group respondents had moderate healing at the assessment 7 pretest respondents (70%), had moderate wound healing at posttest assessment as many as 6 respondents (60%). The statistical test results of the experimental group before and after the intervention with a <0.05 obtained p = 0.005 where H1 was accepted and H0 was rejected, meaning there was an effect of Cork Fish Capsules on the Healing of Sectio Secarea Operation Wounds in the Postpartum Room of Torabelo Sigi Hospital. There is an effect of giving cork fish capsules to healing Sectio secarea surgery wounds in the postpartum room at Torabelo Sigi Hospital.